On the performance analysis of wireless communication systems over α - μ/α - μ composite fading channels. (2019) - Badarneh, Osamah S.; Almehmadi, Fares S.; Aldalgamouni, Taimour
The α - μ/α - μ fading channel model is the result of the product of two independent and non-identically distributed (i.n.i.d.) α - μ variates. As such, in order to study the performance of wireless communication systems in such fading model, the envelopes of the probability density function (pdf) and cumulative distribution function (cdf) must be obtained. To this end, simple and the general closed-form expressions for the pdf and cdf of the product of two independent and non-identically distributed (i.n.i.d.) α - μ variates are obtained. Then based on these expressions, we derive closed-form expressions for the outage probability, the average symbol error probability (SEP) and the nth moment of the signal-to-noise ratio (SNR), and the ergodic channel capacity. The derived expressions are then used to analyse the performance of a wireless communication system. Analytical results are sustained through Monte-Carlo simulations, and a perfect match is reported over a wide range of SNR values and for several values of fading parameters.